Cellular imaging using BODIPY-, pyrene- and phthalocyanine-based conjugates. Issue 2 (15th January 2018) - Bizet, Faustine; Ipuy, Martin; Bernhard, Yann; Lioret, Vivian; Winckler, Pascale; Goze, Christine; Perrier-Cornet, Jean-Marie; Decréau, Richard A.
Graphical abstract: Abstract: Fluorescent Probes aimed at absorbing in the blue/green region of the spectrum and emitting in the green/red have been synthesized (as the form of dyads-pentads), studied by spectrofluorimetry, and used for cellular imaging. The synthesis of phthalocyanine-pyrene 1 was achieved by cyclotetramerization of pyrenyldicyanobenzene, whereas phthalocyanine-BODIPY 2c was synthesized by Sonogashira coupling between tetraiodophthalocyanine and meso-alkynylBODIPY. The standard four-steps BODIPY synthesis was applied to the BODIPY-pyrene dyad 3 starting from pyrenecarbaldehyde and dimethylpyrrole. 1 H, 13 C, 19 F, 11 BNMR, ICP, MS, and UV/Vis spectroscopic analyses demonstrated that 2c is a mixture of BODIPY-Pc conjugates corresponding to an average ratio of 2.5 BODIPY per Pc unit, where its bis, tris, tetrakis components could not be separated. Fluorescence emission studies (μM concentration in THF) showed that the design of the probes allowed excitation of their antenna (pyrene, BODIPY) in the blue/green region of the spectrum, and subsequent transfer to the acceptor platform (BODIPY, phthalocyanine) followed by its emission in the green/red (with up to 140–350 nm overall Stokes shifts). The fluorescent probes were used for cellular imaging of B16F10 melanoma cells upon solubilization in 1% DMSO containing RPMI or upon encapsulation in liposomes (injection method). Probes were used at 1–10 μM concentrations, cells were fixed with methanol and imaged by biphoton and/or confocal microscopy, showing that probes could achieve the staining of cells membranes and not the nucleus.